2013
DOI: 10.1097/mcg.0b013e318264181d
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis in Human Immunodeficiency Virus

Abstract: Background and Aims Abnormal liver enzymes (LE) are common in those infected with HIV. Histologic data on those with abnormal LE without viral hepatitis are lacking. Methods HIV positive subjects without HCV, HBV, alcohol abuse, and DM with more than 1 abnormal LE, defined as 1.25 ULN in AST, ALT, or ALP, over 6 months were included. Subjects underwent a 2 hr oral glucose tolerance test, fasting lipids, insulin and glucose for insulin resistance (IR) by HOMA-IR and DEXA for fat distribution. Biopsies were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…The study populations included HIV+ patients who either had steatosis or were coinfected with HCV. The first cohort consisted of HIV+ patients without HCV with at least 5% steatosis on a liver biopsy (12). The second cohort consisted of HIV-HCV patients.…”
Section: Methodsmentioning
confidence: 99%
“…The study populations included HIV+ patients who either had steatosis or were coinfected with HCV. The first cohort consisted of HIV+ patients without HCV with at least 5% steatosis on a liver biopsy (12). The second cohort consisted of HIV-HCV patients.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of hepatic steatosis is common in those with HIV, including those with HIV-HCV coinfection [1][2][3][4][5], and may be due to the high prevalence of the metabolic syndrome in those with HIV [43]. The prevalence of steatosis in the present cohort (27%) is at the lower end of the spectrum compared to past reports on HIV-HCV coinfection (23-75%) [1] and is related to BMI, obesity, and dyslipidemia, but not to diabetes and hypertension-two components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis is common in patients living with human immunodeficiency virus (HIV), including those coinfected with chronic hepatitis C virus (HCV) [1,2]. In studies of HIV patients at risk for steatosis (e.g., increased liver enzymes) without HCV using liver histology as reference standard, steatosis was detected in 60%-69% [2][3][4][5] compared to 23%-75% of those with HIV-HCV coinfection [1] and 40%-86% of those with chronic HCV without HIV [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 Sterling et al showed that NAFLD is around 26%, and the only clinical or laboratory feature associated with biopsy-proven steatosis was γ-glutamyl transpeptidase and insulin resistance. 43 NAFLD is also seen in HIV patients who are coinfected with hepatitis C. 44 , 45 The only effective therapy for NAFLD is weight loss, and the use of statins with NAFLD appears to be safe and effective.…”
Section: Why Is Dyslipidemia In Hiv Patients a Challenge To Manage?mentioning
confidence: 99%